Comparison for the effects of different components of temperature variability on mortality - Wen, Bo (2024)
Funding Information: This study was supported by the Australian Research Council (DP210102076) and the Australian National Health and Medical Research Council (GNT2000581). BW by China Scholarship Council (number 202006010043); WY by China Scholarship Council (number 202006010044); SL by an Emerging Leader Fellowship of the Australian National Health and Medical Research Council (number GNT2009866); JK and AU by the Czech Science Foundation (project number 20\u201328560S); NS by the National Institute of Environmental Health Sciences-funded HERCULES Center (P30ES019776); S-CP and YLG by the Ministry of Science and Technology (Taiwan; MOST 109\u20132621-M-002\u2013021); YH by the Environment Research and Technology Development Fund (JPMEERF15S11412) of the Environmental Restoration and Conservation Agency; MdSZSC and PHNS by the S\u00E3o Paulo Research Foundation (FAPESP); ST by the Science and Technology Commission of Shanghai Municipality (grant number 18411951600); HO and EI by the Estonian Ministry of Education and Research (IUT34\u201317); JM by a fellowship of Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnlogia (SFRH/BPD/115112/2016); AG by the Medical Research Council UK (grant IDs: MR/V034162/1 and MR/R013349/1), the Natural Environment Research Council UK (grant ID: NE/R009384/1), and the EU's Horizon 2020 project, Exhaustion (grant ID: 820655); AS, SR, and FdD by the EU's Horizon 2020 project, Exhaustion (grant ID 820655); VH by the Spanish Ministry of Economy, Industry and Competitiveness (grant ID PCIN-2017\u2013046); AT by MCIN/AEI/10.13039/501100011033 (grant CEX2018-000794-S); YG by Career Development Fellowship (number GNT1163693) and Leader Fellowship (number GNT2008813) of the Australian National Health and Medical Research Council; Statistics South Africa kindly provided the mortality data, but had no other role in the study. This Article is published in memory of Simona Fratianni who helped to contribute the data for Romania. Publisher Copyright: © 2024